Sorghum yield response to deficit irrigation - Klocke, N. L.; Currie, R. S.; Tomsicek, D. J.; Koehn, J. W. (My University, 2012)
Because dwindling water supplies are limiting crop production, a field study was conducted during 2005-2009 in southwest Kansas to determine the yield response of grain sorghum to irrigation and evapotranspiration (ET[subscript]c) and to measure plant growth parameters and soil water use. Sorghum was grown in a five-year rotation of corn-cornwheat-sorghum-sunflower. Six irrigation treatments were imposed by applying 25 mm of irrigation every 6 to 26 days. Wheat stubble covered 59% to 68% of the soil surface soon after sorghum planting. Sorghum growth stages were not affected by irrigation treatments except maturity in the drier treatments. The soil retained nearly the same amount of dormant season precipitation across all irrigation treatments (34% to 41%), but the sorghum receiving the least irrigation was able to use 56 mm more stored soil water during the following growing season than in the fully irrigated treatment. Grain yield (GY) and total dry matter (DM) decreased significantly as irrigation decreased, but the GY and DM produced by the least irrigation were 91% and 89% of the full irrigation, respectively. Crop evapotranspiration (ET[subscript]c) decreased significantly (from 527 to 459 mm) as irrigation decreased. Because measured ET[subscript]c for the driest treatment was 87% of fully irrigated ET[subscript]c, a linear regression of GY data with respect to ET[subscript]c was not realistic until threshold values of ET[subscript]c (ET[subscript]c required to produce the first increment of grain) from prior field research were added to the data set. GY increased linearly with added irrigation, which was not expected because yield usually responds to irrigation in a diminishing-return fashion. In this case, sorghum, traditionally a dryland crop in the region, was able to utilize stored soil water following wheat to compensate for less irrigation. Small year-to-year variation in GY across irrigation treatments indicates that sorghum would be a good crop when water is very limited and would reduce potential income risk among years. Sorghum planted in part of an irrigated field would allow more water to be applied to a companion crop, such as corn, which needs more water but has more income potential.
Keywords: Deficit irrigation; Irrigation; Irrigation management; Limited irrigation; Sorghum